Analysis of Key Factors on Thrift Shopping Purchase Decisions - Ariyani, Asri Dwi; Asyiqin, Nurul; Hidayah, Nila; Suryono, Abi; Layli, Meutia; Marsuking, Marsuking; Setiorini, Kusumaningdiah Retno (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The main focus of this study is to examine the influence of several factors, namely brand image, product quality, fashion lifestyle, and product price, on thrift shopping purchasing decisions. This research aims to assess the impact of brand image, product quality, fashion lifestyle, and product price on thrift shopping purchasing decisions, with a case study of the people in Ponorogo Regency. The research method used is quantitative with a simple random sampling technique. Data were collected through questionnaires distributed to 100 respondents who had made thrift shopping purchases. The results of the study show that brand image does not affect thrift shopping purchasing decisions, while product quality, fashion lifestyle, and product price have a significant impact on thrift shopping purchasing decisions.